Relationship of Hydroxychloroquine and Ophthalmic Complications in Patients with Type 2 Diabetes in Taiwan - Hung-Chih Chen (International Journal of Environmental Research and Public Health, 2021)
The purpose of this study is to evaluate the relationship between hydroxychloroquine (HCQ) and diabetic retinopathy (DR) via the national health insurance research database (NHIRD) of Taiwan. All patients with newly diagnosed type 2 diabetes (n = 47,353) in the NHIRD (2000–2012) were enrolled in the study. The case group consists of participants with diabetic ophthalmic complications; 1:1 matching by age (±1 year old), sex, and diagnosis year of diabetes was used to provide an index date for the control group that corresponded to the case group (n = 5550). Chi-square test for categorical variables and Student’s t-test for continuous variables were used. Conditional logistic regression was performed to estimate the adjusted odds ratio (aOR) of DR. The total number of HCQ user was 99 patients (1.8%) in the case group and 93 patients (1.7%) in the control group. Patients with hypertension (aOR = 1.21, 95% CI = 1.11–1.31) and hyperlipidemia (aOR = 1.65, 95% CI = 1.52–1.79) significantly increased the risk of diabetic ophthalmic complications (p < 0.001). Conversely, the use of HCQ and the presence of rheumatoid diseases did not show any significance in increased risk of DR. HCQ prescription can improve systemic glycemic profile, but it does not decrease the risk of diabetic ophthalmic complications.